Analysis of the Hail Phenomenon in Bistrița-Năsăud County in 2024: Localization, Impact, Perception, and Mitigation - BARTA, Andras-István; RABOȘAPCA, Irina; BILAȘCO, Ștefan; MOLDOVAN, Aurelian Cosmin; MIHĂIESCU, Tania (Studia Universitatis Babeș-Bolyai Geographia, 2024)
Analysis of the hail phenomenon in Bistrița-Năsăud County in 2024: localization, impact, perception, and mitigation. This study examines the hail phenomenon that impacted Bistrița-Năsăud County during the period 2022-2024, with a particular focus on the significant hail events of 2024. The research integrates climatological data, meteorological observations, and locally sourced information to evaluate the frequency, localization, and intensity of hail across the region. Specific emphasis is placed on areas such as Săsarm, where the June 2024 hailstorm inflicted severe damage on households, agricultural infrastructure, and public amenities. The study not only documents the material and economic consequences but also investigates the community’s perception of the implemented preventive and mitigation strategies, such as anti-hail systems and agricultural insurance policies. Findings underline that while some measures were in place, there remains a critical need for more robust and effective climate risk management approaches, particularly in high-risk areas like Bistrița-Năsăud County. Enhanced public awareness campaigns and investment in adaptive technologies are identified as key steps toward increasing community resilience.